The kings of Clonmel - Flanagan, John (John Anthony) (New York, NY : Philomel Books, 2010)
Halt, Will, and Horace set out for Hibernia, where a quasi -religious group, the Outsiders, is sowing confusion and sedition, and they find that secrets from Halt's past may hold the key to restoring order before the last kingdom is undermined.
Keywords: Insurgency -- Juvenile fiction; Kings, queens, rulers, etc. -- Juvenile fiction; Cults -- Juvenile fiction; War stories; Fantasy fiction